Influência do agente precipitante na síntese de catalisadores Cu-ZrO2 aplicados na conversão de glicerol a acetol e propilenoglicol - Corrêa, João Vítor Soares (Universidade Federal de São Carlos, 2021)
Biodiesel production by transesterification reaction generates large amounts of glycerol as a by-product. The development of chemical routes to use glycerol as raw material for products with high added value is essential to foment the biodiesel industry. Therefore, acetol emerge as an interesting product derived from glycerol that can be an intermediary for other chemical products, such as propylene glycol, pyruvic acid, and propionic acid, among others. In this work, the study of the heterogeneous catalytic conversion of glycerol to acetol and other products of interest was evaluated. For that, copper and zirconium catalysts were synthesized with different compositions by co-precipitation method, which evaluated the influence of precipitating agents: triethylamine (Et3N), sodium hydroxide (NaOH), and sodium carbonate (Na2CO3). The materials were characterized by X-ray diffraction, temperature-programmed reduction, N2 physisorption, selective Cu oxidation by N2O, NH3 temperature-programmed desorption, and in situ infrared analysis with pyridine. Characterizations results showed that, in addition to the mass composition, the precipitating agent used affected the physicochemical properties of the catalysts and, consequently, their catalytic performance. Reactions tests were carried out in a batch reactor and after previous evaluation, the reaction parameters were fixed at T = 180 °C, stirring at 800 rpm, V = 30 mL (80% aqueous glycerol(m/m)), during 1 h, with an initial pressure of 1 atm (N2) and 300 mg of catalyst. The catalysts showed activity for the dehydration reaction of glycerol to acetol and subsequent in situ hydrogenation to propylene glycol without adding H2 to the reaction medium. It was observed a correlation between the concentration of acidic sites and the selectivity in the conversion of glycerol to acetol, propylene glycol, and other products. Furthermore, the strength distribution of acidic sites, particle size, and textural properties, such as porosity can regulate the selectivity of the reaction. Finally, the reuse tests showed moderate loss of catalyst activity, although the used catalysts did not go through a reactivation step between each reaction.
Influence of the precipitating agent on the synthesis of Cu-ZrO2 catalysts applied in the conversion of glycerol to acetol and propylene glycol
Keywords: Catálise heterogênea; Glicerol; Acetol; Propilenoglicol; Cobre; Zircônio; Heterogeneous catalysis; Glycerol; Propylene glycol; Copper; Zirconium; ENGENHARIAS::ENGENHARIA QUIMICA